The occurrence of Salmonella in raw and ready‐to‐eat bean sprouts and sprouted seeds on retail sale in England and Northern Ireland. (February 2016) - Sadler‐Reeves, L.; Aird, H.; de Pinna, E.; Elviss, N.; Fox, A.; Kaye, M.; Jorgensen, F.; Lane, C.; Willis, C.; McLauchlin, J.
Abstract: A total of 554 samples of bean sprouts or other sprouted seeds were collected at retail sale and submitted to nine Official Control Laboratories in England and Northern Ireland during January to March 2011. Samples (100 g) were tested for the presence of Salmonella using the EN ISO 6579:2002 method. Products labelled as ready‐to‐eat comprised 23% of the samples and 61% were labelled as raw or to‐cook: the remaining 12% had no indication if the food was intended as ready‐to‐eat or ready‐to‐cook, and 4% were not recorded. Salmonella spp. were detected from four samples of mung‐bean sprouts (0·7% of all the 554 samples) and all four isolates were confirmed as Salmonella enterica serovar Abaetetuba (11 : k : 1, 5). Two of the samples where Salmonella was detected were sold as ready‐to‐eat (labelled 'rinse and serve' only): The remaining two were from samples labelled as ready‐to‐cook. Significance and Impact of the Study: Consumption of sprouted seeds have been associated with infections from a range of foodborne pathogens, particularly Salmonella and shigatoxin producing Escherichia coli (STEC). However, there is limited data (including that from EU monitoring) on foodborne pathogens in samples of this food type which are not associated with outbreaks of infection. Out of 554 raw and ready‐to‐eat bean sprouts and sprouted seeds sampled at retail, Salmonella spp . was detected from four samples. This study illustrated the potential of this product to be contaminated with a human pathogen and the importance of considering the intended use and preparation of specific food in assessing microbiological risks. Abstract : Significance and Impacts of the Study: Consumption of sprouted seeds have been associated with infections from a range of foodborne pathogens, particularly Salmonella and shigatoxin producing Escherichia coli (STEC). However, there is limited data (including that from EU monitoring) on foodborne pathogens in samples of this food type which are not associated with outbreaks of infection. Out of 554 raw and ready‐to‐eat bean sprouts and sprouted seeds sampled at retail, Salmonella spp . was detected from four samples. This study illustrated the potential of this product to be contaminated with a human pathogen and the importance of considering the intended use and preparation of specific food in assessing microbiological risks.